Delaware politics and government - Boyer, William W. (Politics and governments of the American states., 2009)
This volume provides a comprehensive analysis of both the historical and the contemporary dimensions of the politics and government of the "First State." Once a sparsely populated, agrarian, and relatively insignificant polity, Delaware has become a densely and diversely populated financial and legal center often called the "corporation capital of the world." Delaware's prime location has been central to its development and transition from a goods-producing economy to a fast-growing, service-based economy. Despite its diminutive size, Delaware is, in many ways, the nation's preferred corporate